(untitled) (Theatrum historiae, 2008)
The so-called “just war theory” is one of the few instances in the history of human endeavors when organized violence (i.e. war) directly meets philosophy. Apparently, almost every known human community have had knowledge about warfare and every one of them created more or less elaborate cultural constraints on its grim reality. In this light, the just war theory needs to be viewed as a cultural construct made by members of the so-called western civilization to put limitations to their “way of war”. Whether or not such a distinct way of war actually exists does not matter, because what is clear for sure is that, throughout the centuries, a distinct thinking about war has indeed developed in the West, the fact that makes the contemporary just war theory (as enshrined in international institutions and legal documents) invariably Eurocentric. Anyone who considers the problems of war in 21st century must keep this in mind in order to be able to understand the problem of human organized violence in its complexity. The purpose of this article is to bring a short comprehensive (and necessarily selective) survey of the theory’s lineage from its beginnings towards full and systematized form created in Europe in early 17th century. With little space for deep analysis, it tries to list the most important authors and their contributions to development of the theory, while putting their thoughts into historical contexts. In this way, the text starts with basically realist attitudes towards warfare in classical Greece (as exemplified by Thukydides), then moves to Plato’s and Aristoteles’ first efforts to connect warfare with morality (and with their utterly ethnocentric interpretation of it). Then, with little pause made for Roman “utilitarian turn” in the just war thinking, the text focuses its attention at Christian attitudes towards warfare, their efforts to accommodate it in their system of beliefs (as with Tertullian, Origen, or Ambrose), and their success in creating a suitable just war theory based on ideas of former ancient authors as well as on Christian teachings (as with St. Augustine). With further development of this idea for the purposes of the Crusades and the late Middle Ages in general come the well established ways to justify war: a just cause, sovereign authority, and the aim of peace. While further development of this theory during 15th and 16th century brings in the growing distinction between defensive (even private) and offensive (punishing) war, alternative discourses are also mentioned in the works of Erasmus of Rotterdam, Machiavelli, Thomas More, Martin Luther, and others. The text finishes with the just war theory being systematized by Hugo Grotius, whose work is understood here as a peak of the above mentioned development on the one hand, as well as a core of the just war theory in the future on the other.